Using mobile device affordances for news offering: an analysis of latin american newspaper apps - Amarante, Erivelto (2021)
This study deals with the use of mobile device affordances in news applications. It aims to identify how media groups take advantage of the devices’ native resources to offer informative content and services, such as the weather forecast. To that end, all the newspaper applications associated with the Grupo de Diarios América (GDA), an entity that gathers publications from 11 countries of the region, were analyzed. The result revealed that most newspapers take advantage of the potential provided by affordances to their applications in a residual way. Although mobile phones are the main form of Internet access in the continent, we found newspapers without an application in our sample, which portrays a still challenging scenario in the face of new mobile technologies.